APPLYING TIME TOKEN MODEL TOWARD STUDENTS’ VOCABULARY SKILL - Asep Kurniawan (TULIP (Tulisan Ilmiah Pendidikan), 2016)
In this research, the researchers found a problem, that is the weakness of students in English, for example in vocabulary, Memorizing vocabulary that is usually done is always memorizing in a conventional way, so it is easy to forget and difficult to memorize. That's a big problem for memorizing vocabulary, especially for conversation. Based on the formulation of the research above, the objective of the research were formulated to identify whether time token Arends can improve the students’ vocabulary skills. The research that the researcher do here is a study literature, using a qualitative approach. In collecting the required data, the researcher uses books as primary data and previous theses and journals for secondary data, while in the discussion using the time token method, which is a method that is expected to be able to make students active in learning. According to references, the time token model can increase students' interest in speaking English through vocabulary, and students are active in expressing their opinions.